2002
DOI: 10.1038/sj.bjc.6600122
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of treatment response to high-dose salvage chemotherapy in patients with relapsed germ cell cancer using [18F]FDG PET

Abstract: To assess the ability of [ 18 F]fluorodeoxyglucose positron emission tomography for the early prediction of response in patients with relapsed metastatic germ cell tumours undergoing salvage high-dose chemotherapy. The role of positron emission tomography was compared with established means of tumour response assessment such as CT scans/MRI and serum tumour marker changes. In addition, positron emission tomography was compared with a current prognostic score which differentiates three prognostic groups with fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…FDG-PET performed early in the course of salvage treatment has provided independent prognostic information [23]. In particular, FDG-PET could be useful when mismatch between tumor marker and CT changes occurs and salvage surgery could be considered as an option [23,24]. However, larger trials are needed before drawing any firm conclusion.…”
Section: Early Prediction Of Treatment Responsementioning
confidence: 99%
See 2 more Smart Citations
“…FDG-PET performed early in the course of salvage treatment has provided independent prognostic information [23]. In particular, FDG-PET could be useful when mismatch between tumor marker and CT changes occurs and salvage surgery could be considered as an option [23,24]. However, larger trials are needed before drawing any firm conclusion.…”
Section: Early Prediction Of Treatment Responsementioning
confidence: 99%
“…In a recent study, the role of FDG-PET has been compared with established means of tumor response assessment such as CT and serum tumor marker changes in 23 patients with relapsed GCT treated with salvage chemotherapy [23]. FDG-PET performed early in the course of salvage treatment has provided independent prognostic information [23]. In particular, FDG-PET could be useful when mismatch between tumor marker and CT changes occurs and salvage surgery could be considered as an option [23,24].…”
Section: Early Prediction Of Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, 21 studies were excluded for undesirable article types (n=21), not written in English (n=6), and insufficient data (n=4), letter (n=2), case report (n=1), and review (n=8). Thus, 16 studies were included in our final dataset for the meta-analysis (Cremerius et al, 1998;Albers et al, 1999;Cremerius et al, 1999;Hain et al, 2000;Bokemeyer et al, 2002;Spermon et al, 2002;Tsatalpas et al, 2002;Lassen et al, 2003;De Santis et al, 2004;Becherer et al, 2005;de Wit et al, 2008;Hinz et al, 2008;Oechsle et al, 2008;Akbulut et al, 2011;Bachner et al, 2012;Siekiera et al, 2012). The flowchart of study selection was shown in Figure 1.…”
Section: Study Selection and Characteristics Of Studies In Our Analysismentioning
confidence: 99%
“…However, the role of 18 F-FDG PET in staging nonseminomatous residues is limited because 18 F-FDG PET cannot differentiate mature teratoma from necrosis and fibrosis (6,7,(9)(10)(11)(12). In predicting early therapy response, 18 F-FDG PET may have a role in poorprognosis GCT patients, as has been addressed in a pilot study with 19 patients (13,14).…”
mentioning
confidence: 99%